The Determinants of Growth In Banking Sector: Time Series Analysis of Conventional And Islamic Banking In Pakistan - Iqbal, Muhammad Saeed; Sofi, Mohd Fikri (University of Management and Technology, 2023)
A well-developed financial and banking system efficiently transforms savings into investments. The banking system of Pakistan is based on a dual structure of conventional and Islamic banking. The current study aims to identify the factors that determine growth in the banking industry of Pakistan, keeping in view both conventional and Islamic banking. For this purpose, the ARDL model was applied on the time series data of Pakistan for the period 2007-2022. The data was taken from the State Bank of Pakistan (SBP). The variable ‘investment’ was used as a proxy to measure growth in the banking sector, comprising both conventional and Islamic banking sectors. The results of the empirical analysis indicated that growth in deposit, growth in GDP, and population growth are the main determinants of growth in the banking sector of Pakistan. Based on the findings of the study it is suggested that measures must be taken to increase deposits in both systems of banking by giving various incentives to households